PENGARUH PROGRAM KESEHATAN & KESELAMATAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PT. SURYA BRATASENA PLANTATION PELALAWAN - Eka Ristiani; Machasin '; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The Performance which not yet adequate represent a problems which often faced by company in its effort to increase advantage to reach. Problem of performance closely related with attainment of company target, because labour represent one of the primary factor to company in reaching target which have been specified. Disability of company in effort to increase employees performance represent an constraint faced by each every company. Target of this research is to see influence of Medicare & working safety and environment work to employees performance part of production at PT. Surya Bratasena Plantation Pelalawan. Population in this research amount to 175 people. While technique intake of sampel by sampling cluster with election of sampling accidental sampel. thereby known the amount of as many sampling 64 date. Analysis use doubled linear regression method with program of SPSS 18. Pursuant to result of research known that health & working safety by parsial and simultan have an effect on signifikan to employees performance part of production at PT. Surya Bratasena Plantation Pelalawan.Keywords: Health & Working Safety, Environmental of work And Performance Employees.